Thermal stability enhancement of oriented polyethylene by formation of epitaxial shish-kebab crystalline structure. (January 2022) - He, Wenjun; Kong, Chen; Cai, Yudong; Ye, Lin; Chen, Shangtao; Li, Shuanghong; Zhao, Xiaowen
Highlights: RENA was used to induce PE to form stable epitaxial oriented crystalline structure. At low draw ratio, new anisotropic shish-kebab crystalline structure formed by aging. At high draw ratio, highly oriented shish-kebab structure was retained after aging. Oriented PE-RENA showed high dimensional/mechanical stability at high temperature. Abstract: Oriented polyethylene (PE) products usually exhibit thermodynamic instability in oriented crystalline structure under high temperature during long term service. In this work, self-assembly rare-earth nucleating agent (RENA) was innovatively introduced to fabricate oriented PE and induced PE molecules to form stable epitaxial oriented crystalline structure. Compared with oriented neat PE, oriented PE-RENA showed much higher dimensional/strength retention during aging, which reached as high as 90.13%/86.46% after aging at 100 °C for 1000 h, exhibiting high dimensional/mechanical stability. At low draw ratio, PE-RENA exhibited hybrid oriented shish-kebab structure, for which oriented RENA assembly acted as shish structure and PE lamellae acted as kebab structure, while, after aging, new stable anisotropic shish-kebab crystalline structure formed and the crystallinity ( X c ) changed slightly. At high draw ratio, highly oriented shish-kebab structure formed, most of which was retained after aging and the changes of X c /orientation degree was insignificant, while the molecular mobility in crystalline phase/intermediate phase was weakened, exhibiting enhanced thermal stability in oriented crystalline structure. Graphical abstract: Image, graphical abstract